Comparing the Contribution of Visible‐Light Irradiation, Gold Nanoparticles, and Titania Supports in Photocatalytic Nitroaromatic Coupling and Aromatic Alcohol Oxidation. (13th June 2016) - Zhao, Jian; Ke, Xuebin; Liu, Hongwei; Huang, Yiming; Chen, Chao; Bo, Arixin; Sheng, Xianliang; Zhu, Huaiyong
Abstract : Under visible‐light irradiation, gold nanoparticles (Au NPs) supported by titania (TiO2 ) nanofibers show excellent activity and high selectivity for both reductive coupling of nitroaromatics to corresponding azobenzene or azoxylbenzene and selective oxidation of aromatic alcohols to corresponding aldehydes. The Au NPs act as active centers mainly due to their localized surface plasmon resonance (LSPR) effect. They can effectively couple the photonic energy and thermal energy to enhance reaction efficiency. Visible‐light irradiation has more influence on the reduction than on the oxidation, lowering the activation energy by 24.7 kJ mol −1 and increasing the conversion rate by 88% for the reductive coupling, compared to merely 8.7 kJ mol −1 and 46% for the oxidation. Furthermore, it is found that the conversion of nitroaromatics significantly depends on the particle size and specific surface area of supported Au NPs; and the catalyst on TiO2 (B) support outperforms that on anatase phase with preferable ability to activate oxygen. In contrast, for the selective oxidation, the effect of surface area is less prominent and Au NPs on anatase exhibit higher photo‐catalytic activity than other TiO2 phases. The catalysts can be recovered efficiently because the Au NPs stably attach to TiO2 supports by forming a well‐matched coherent interface observed via high‐resolution TEM. Abstract : Under visible‐light irradiation, Au nanoparticles (Au NPs) on TiO2 nanofiber can effectively drive reductive coupling of nitroaromatics and selective oxidation of aromatic alcohols. The contributions of visible‐light irradiation, Au NPs, and TiO2 supports to the catalytic performance for these two typical reactions are different. Visible light influences reduction more than oxidation.